Torsion-resistant cable for 35kV wind driven generator
By using a specific conductor twisted structure, anti -twist -resistant layer, and optimized external care covering material in the wind power generator cable, the stability and durability of the wind power generation cable under high torsional conditions have been solved. Properly improved resistance.
Patent Information
- Application Number
- CN202411936684.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Cables in wind turbines need to have high torsion resistance, and existing cables lack stability and durability under high torsion conditions.
A 35KV wind power generator is designed to use a twist -resistant cable, using a single -line arrangement form with a conductor of 2 × 8+1 × 6 for a rectangular arrangement of the beam tie and 1+6+12 to increase the reinforcement layer. Fura fiber woven, and adds a star-shaped combed polytrathne-G-polymethyl acrylic metharocoltain, liquid-ended amino-pyramid rubber, and silicon nanotuba.
It significantly improves the resistance and stability of the cable, and can be kept intact under high to reversing conditions without breakdown.
Smart Images

Figure CN119381072A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, in particular to a torsion-resistant cable for a 35kV wind turbine generator. Background Art
[0002] With the rapid development of my country's economy, the acceleration of industrialization and urbanization, energy demand has grown rapidly. As people pay more attention to environmental protection, clean energy, energy conservation and emission reduction, they optimize the energy structure, reduce the proportion of petrochemical energy, and vigorously develop new energy. Renewable energy such as wind energy, photovoltaic solar energy, biomass energy and geothermal energy have ushered in development opportunities.
[0003] The development of the wind power industry has given rise to the demand for special cables for wind turbines. For example, the power and control signal cables in the uppermost section of the tower need to rotate continuously with the wind turbine, which puts higher requirements on the cable's anti-torsion performance. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a torsion-resistant cable for a 35kV wind turbine.
[0005] The technical solutions adopted are as follows: A 35kV torsion-resistant cable for a wind turbine generator, comprising a cable core and a ground wire, wherein the cable core and the ground wire are fixed by being coated with an anti-torsion reinforcement layer and an outer sheath layer; The outer sheath layer is prepared from the following raw materials in parts by weight: 90-100 parts of polyvinyl chloride, 5-10 parts of liquid amino-terminated nitrile rubber, 5-10 parts of star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer, 10-20 parts of silica nanotubes, 3-5 parts of composite lead stabilizer, 5-10 parts of carbon black, 0.1-1 parts of paraffin, 1-2 parts of stearic acid, 1-3 parts of phosphate flame retardant, 0.1-0.5 parts of antioxidant and 20-40 parts of plasticizer.
[0006] Furthermore, the cable core comprises a conductor, a conductor shielding layer, an EPR insulating layer and an insulating shielding layer from the inside to the outside.
[0007] Among them, the conductor is the fifth type of soft copper co-directional stranded wire structure, and the production process is wire drawing-bundle twisting-re-twisting. The wire drawing uses a single wire of 1.75±0.05mm, and is drawn into a single wire of 0.38mm under the conditions of an annealing coefficient of 95%, a speed of 16-22m / s, and 14 stretching passes. Then, an automatic high-speed wire bundler is used to bundle the 0.38mm wire in a single wire arrangement of 2×8+1×6 (2 strands of 8 0.38mm wires and 1 strand of 6 0.38mm wires are twisted together) to control the pitch ratio to 18-20 times for bundle twisting, and the twisting direction is left-handed. Then, it is re-twisted by a 6+12+18 / 500 cage twisting machine. According to the arrangement of 1+6+12, the inner layer pitch ratio is controlled at 18-20 times, and the outer layer pitch ratio is controlled at 16-18 times. The twisting directions are all in the same left direction to form a conductor; The cable bundles are twisted in a 2×8+1×6 single-wire arrangement and a 1+6+12 double-twisted arrangement. This structural design helps to improve the overall stability and torsion resistance of the cable. The control of the pitch ratio ensures the tightness and uniformity of the strands, thereby enhancing the torsion strength of the cable. The same-direction twisting means that all twisting directions are left-handed. This same-direction twisting can reduce the internal stress of the cable when it is twisted, and improve the stability and durability of the cable.
[0008] Furthermore, the torsion-resistant reinforcement layer is woven from Kevlar fibers according to 8 spindles / 2000D, 4 spindles on each side, with a pitch of 110-130 mm, cross-woven, and each spindle is woven evenly at intervals. The weaving density is 20-26%. The design of 4 spindles on each side makes the Kevlar fibers evenly distributed in the cable, which can provide balanced support when the cable is twisted, avoiding damage caused by excessive local force.
[0009] Furthermore, the preparation method of the star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer is as follows: The star-shaped polybutadiene is synthesized by a formic acid-hydrogen peroxide in-situ method to obtain a star-shaped epoxidized polybutadiene, and the star-shaped epoxidized polybutadiene is subjected to an incomplete esterification reaction with 2-bromoisobutyryl bromide under the action of water to obtain a star-shaped brominated polybutadiene, and then the star-shaped brominated polybutadiene is used as an initiator, cuprous chloride and cupric chloride are used as a catalyst and a regulator respectively, and N,N,N',N",N"-pentamethyldiethylenetriamine is used as a ligand, and methyl methacrylate polymerization is initiated by an ATRP method to finally obtain the star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer.
[0010] Furthermore, the molar ratio of the epoxy group to 2-bromoisobutyryl bromide in the star-shaped epoxidized polybutadiene is 1:0.1-0.8. By controlling the molar ratio of the epoxy group to 2-bromoisobutyryl bromide in the star-shaped epoxidized polybutadiene, the number of residual epoxy groups in the star-shaped epoxidized polybutadiene can be controlled. Controlling the number of epoxy groups can control the cross-linking density of the epoxy groups and the amino groups in the outer sheath layer, thereby achieving the purpose of improving the tensile properties of the outer sheath.
[0011] Furthermore, the molar ratio of bromine atoms in the star-shaped brominated polybutadiene to methyl methacrylate is 1:10-40.
[0012] Further, the preparation method of silicon dioxide nanotubes is as follows: The sepiolite is crushed and washed with deionized water, first added to a hydrochloric acid solution to remove impurities, the reaction solution is filtered, the solid is collected and washed thoroughly with deionized water, then added to a polyvinyl pyrrolidone solution, ultrasonically treated, and then sodium borohydride is added. The reaction solution is reacted at 50-70°C for 1-5h, and finally the product is collected, washed thoroughly with deionized water, and then dried.
[0013] Furthermore, the phosphate flame retardant is any one or more combinations of tris(isopropylphenyl) phosphate, tris(2-chloroethyl) phosphate, and tris(2-chloropropyl) phosphate.
[0014] Furthermore, the antioxidant is any one or more combinations of antioxidant 1010, antioxidant 1076, antioxidant 245, and antioxidant 168.
[0015] Furthermore, the plasticizer is any one or more combinations of dimethyl phthalate, diethyl phthalate, di-n-butyl phthalate, dioctyl phthalate, butyl benzyl phthalate, and diisononyl phthalate.
[0016] Beneficial effects of the present invention: The present invention provides a torsion-resistant cable for a 35kV wind turbine generator. The conductor is twisted in a bundle in a 2×8+1×6 single-wire arrangement and a 1+6+12 double-twisted arrangement. This structural design helps to improve the overall stability and torsion resistance of the cable. The control of the pitch ratio ensures the tightness and uniformity of the twisted wire, thereby enhancing the torsion strength of the cable. The same-direction twisting means that all twisting directions are left-handed. This same-direction twisting can reduce the internal stress of the cable when it is twisted, and improve the stability and durability of the cable. The torsion-resistant reinforcement layer is woven from 8 spindles / 2000D of Kevlar fiber, 4 spindles on the front and back, with a pitch of 110-130mm, cross-woven, and each spindle is evenly spaced and woven. The weaving density is 20-26%. The design of 4 spindles on the front and back makes the Kevlar fiber evenly distributed in the cable, which can provide balanced support when the cable is torsion, avoiding damage caused by excessive local force; The outer sheath layer of the present invention has excellent tensile properties and can significantly improve the torsion resistance of the cable. The star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer has a special star-shaped comb-shaped structure and has good compatibility with PVC. It also contains polymethyl methacrylate side chains and epoxy groups. The star-shaped comb-shaped structure inhibits the strong interaction between the polar C-Cl bonds of the PVC chain and can strengthen the outer sheath material by dissipating the energy of external forces. Polymethyl methacrylate is conducive to promoting the brittle-tough transition of the PVC matrix, generating a large amount of free volume and increasing the movement opportunities of macromolecules, so the tensile properties are improved. The epoxy group can react with the liquid end amino nitrile. The epoxy groups in the rubber are cross-linked, which plays a positive role in improving the tensile properties of the outer sheath layer. The liquid end-amino nitrile rubber has good compatibility with PVC and is easy to form a cellular structure coated with PVC. It is dispersed in the PVC continuous phase to form an "island" structure, inducing the production of silver streaks and shear bands and absorbing energy, which has the effect of toughening and anti-torsion. The silica nanotubes not only have a reinforcing effect, but also, as a highly efficient and environmentally friendly flame retardant, can work together with phosphate flame retardants to improve the fire retardant properties of the outer sheath layer. Of course, the above mechanism is only a guess based on the experimental results, and there may be omissions and errors, but it will not have a negative impact on the creativity of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a schematic diagram of the structure of the cable provided in Example 1, where the reference numerals represent: 1-outer sheath layer, 2-ground wire, 3-torsion reinforcement layer, 4-insulation shielding layer, 5-EPR insulation layer, 6-conductor shielding layer, 7-conductor. DETAILED DESCRIPTION
[0018] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters. Example 1
[0019] A 35kV torsion-resistant cable for wind turbines. Figure 1, consisting of a cable core and a ground wire 2, the cable core and the ground wire 2 are fixed by a torsion-resistant reinforcement layer 3 and an outer sheath layer 1; The cable core includes a conductor 7, a conductor shielding layer 6, an EPR insulating layer 5 and an insulating shielding layer 4 from the inside to the outside; Among them, conductor 7 is the fifth type of soft copper co-directional stranded wire structure, and the production process is wire drawing-bundle twisting-re-twisting. The wire drawing uses a single wire of 1.75±0.05mm, and is drawn into a single wire of 0.38mm under the conditions of an annealing coefficient of 95%, a speed of 16-22m / s, and 14 stretching passes. Then, an automatic high-speed wire bundler is used to bundle and twist the 0.38mm wire in a 2×8+1×6 single wire arrangement form to control the pitch ratio to 18-20 times, and the twisting direction is left-handed. Then, it is re-twisted by a 6+12+18 / 500 cage stranding machine. According to the arrangement of 1+6+12, the inner layer pitch ratio is controlled to 18-20 times, and the outer layer pitch ratio is controlled to 16-18 times. The twisting directions are all in the same left direction, forming conductor 7; The conductor shielding layer 6 is formed by wrapping an aluminum-plastic composite tape, and the insulating shielding layer 4 is formed by wrapping a PET electrical insulating film; The torsion reinforcement layer 3 is made of Kevlar fiber woven according to 8 spindles / 2000D, 4 spindles on the front and back, with a pitch of 110-130mm, cross-woven, and each spindle is evenly spaced and woven, with a weaving density of 20-26%; The outer sheath layer 1 is prepared from the following raw materials in parts by weight: 100 parts of polyvinyl chloride, 8 parts of liquid amino-terminated nitrile rubber, 6 parts of star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer, 15 parts of silica nanotubes, 3 parts of composite lead stabilizer, 10 parts of carbon black, 0.5 parts of paraffin, 2 parts of stearic acid, 2 parts of flame retardant IPPP, 0.25 parts of antioxidant 1010, and 25 parts of plasticizer DOP.
[0020] The preparation method of the star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer is as follows: 9.39 g of 1,3-butadiene cyclohexane solution (1,3-butadiene: cyclohexane = 1:8, V : V), 2.85ml cyclohexane solution of n-butyl lithium (2mol / L) and 0.6ml THF was pressed into a dry round-bottom flask with nitrogen and mixed. The reaction liquid was reacted in a constant temperature water bath at 50°C for 3 hours under nitrogen protection, and then 1.42ml (1.1mol / L) of SiCl4 cyclohexane solution was added. The reaction was continued for 4 hours under insulation. After returning to room temperature, the reaction liquid was precipitated with anhydrous ethanol. The resulting precipitate was vacuum dried at 50°C to constant weight to obtain a crude product. The crude product was extracted with acetone in a Soxhlet extractor for 12 hours to obtain star-shaped polybutadiene. 5g of star-shaped polybutadiene was dissolved in 100ml of toluene, 1.74g of formic acid was added, and 4.2g of hydrogen peroxide was titrated within 30min in a constant temperature water bath at 40°C. After insulation reaction for 2 hours, the reaction liquid was washed with deionized water and the organic phase was separated. Ethanol was added for precipitation. The resulting precipitate was vacuum dried at 50°C to constant weight to obtain star-shaped epoxidized polybutadiene and the epoxidation degree was calculated. Under nitrogen protection, 5g of star-shaped epoxidized polybutadiene was added to 50ml THF, stir to fully dissolve, then add triethylamine, 50ml THF and 1ml deionized water, add 2-bromoisobutyryl bromide dropwise within 30min under ice bath condition, the molar ratio of epoxy group, triethylamine and 2-bromoisobutyryl bromide in star-shaped epoxidized polybutadiene is 1:0.5:0.4, react at room temperature for 48h, pass through activated alumina column, use chloroform as eluent, add ethanol to the eluent for precipitation, and the obtained precipitate is dried under vacuum at 50℃ to constant weight to obtain star-shaped brominated polybutadiene, and the bromine content therein is determined by chemical titration, and the molar ratio of star-shaped brominated polybutadiene, cuprous chloride, cupric chloride, N,N ,N',N",N"-pentamethyldiethylenetriamine was mixed and then methyl methacrylate was added to control the molar ratio of bromine atoms in the star-shaped brominated polybutadiene to methyl methacrylate to be 1:20. After repeated operation of liquid nitrogen freezing-vacuuming-thawing for 3 times, the reaction was carried out in a constant temperature water bath at 50°C for 8 hours, and the polymerization was terminated by ice salt bath. After adding an appropriate amount of THF to dissolve the product, a neutral alumina column was used with THF as the eluent, and ethanol was added to the eluent for precipitation. The resulting precipitate was vacuum dried at 50°C to constant weight to obtain a star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer.
[0021] The preparation method of silica nanotubes is as follows: 100g of sepiolite was crushed and passed through an 80-mesh sieve, and then washed with deionized water to remove water-soluble impurities. Then, it was added to a sufficient amount of 6mol / L hydrochloric acid solution and stirred at room temperature for 12h to remove impurities. The obtained reaction solution was filtered, and the solid was collected and washed with deionized water until neutral and dried. 6g of the obtained product was added to 200ml of 2.91wt% polyvinyl pyrrolidone solution, and ultrasonically oscillated for 30min, then 12g of sodium borohydride was added. The obtained reaction solution was reacted at 65℃ for 3h, and finally the solid product was collected by centrifugation, washed with deionized water and dried.
[0022] The preparation method of the above outer sheath layer is as follows: Weigh each component according to the formula and mix them evenly, ensuring that the mixing temperature does not exceed 120℃. After the material temperature drops to room temperature, place it on an open plastic purifying machine for plasticization, with the front roller temperature at 160±10℃ and the rear roller temperature at 140±10℃. Discharge the material after mixing for 5 minutes, and then preheat it on a flat vulcanizing press at 160℃ and 5MPa for 5 minutes, increase the pressure to 14MPa, keep the pressure unchanged, and hot press for 5 minutes before discharging.
[0023] According to B.4.1 room temperature torsion test and B.4.2-25℃ low temperature torsion test in GB / T 33606-2017, the cable appearance was intact after 10,000 times of 1080° torsion test at room temperature and 5,000 times of 1080° torsion test at low temperature. After torsion, the cable was subjected to AC 50HZ 73.5KV voltage for 60 minutes without breakdown. Example 2
[0024] The method is basically the same as Example 1, except that, in parts by weight, the outer sheath layer is prepared from the following raw materials: 100 parts of polyvinyl chloride, 10 parts of liquid amino-terminated nitrile rubber, 10 parts of star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer, 20 parts of silica nanotubes, 5 parts of composite lead stabilizer, 10 parts of carbon black, 1 part of paraffin, 2 parts of stearic acid, 3 parts of phosphate flame retardant, 0.5 parts of antioxidant, and 30 parts of plasticizer.
[0025] According to B.4.1 room temperature torsion test and B.4.2-25℃ low temperature torsion test in GB / T 33606-2017, the cable appearance was intact after 10,000 times of 1080° torsion test at room temperature and 5,000 times of 1080° torsion test at low temperature. After torsion, the cable was subjected to AC 50HZ 73.5KV voltage for 60 minutes without breakdown. Example 3
[0026] The method is basically the same as Example 1, except that, in parts by weight, the outer sheath layer is prepared from the following raw materials: 90 parts of polyvinyl chloride, 5 parts of liquid amino-terminated nitrile rubber, 5 parts of star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer, 10 parts of silica nanotubes, 3 parts of composite lead stabilizer, 5 parts of carbon black, 0.1 parts of paraffin, 1 part of stearic acid, 1 part of phosphate flame retardant, 0.1 parts of antioxidant, and 20 parts of plasticizer.
[0027] According to B.4.1 room temperature torsion test and B.4.2-25℃ low temperature torsion test in GB / T 33606-2017, the cable appearance was intact after 10,000 times of 1080° torsion test at room temperature and 5,000 times of 1080° torsion test at low temperature. After torsion, the cable was subjected to AC 50HZ 73.5KV voltage for 60 minutes without breakdown. Example 4
[0028] The method is basically the same as Example 1, except that, in parts by weight, the outer sheath layer is prepared from the following raw materials: 100 parts of polyvinyl chloride, 5 parts of liquid amino-terminated nitrile rubber, 10 parts of star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer, 10 parts of silica nanotubes, 5 parts of composite lead stabilizer, 5 parts of carbon black, 1 part of paraffin, 1 part of stearic acid, 3 parts of phosphate flame retardant, 0.1 part of antioxidant, and 30 parts of plasticizer.
[0029] According to B.4.1 room temperature torsion test and B.4.2-25℃ low temperature torsion test in GB / T 33606-2017, the cable appearance was intact after 10,000 times of 1080° torsion test at room temperature and 5,000 times of 1080° torsion test at low temperature. After torsion, the cable was subjected to AC 50HZ 73.5KV voltage for 60 minutes without breakdown. Example 5
[0030] The method is basically the same as Example 1, except that, in parts by weight, the outer sheath layer is prepared from the following raw materials: 90 parts of polyvinyl chloride, 10 parts of liquid amino-terminated nitrile rubber, 5 parts of star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer, 20 parts of silica nanotubes, 3 parts of composite lead stabilizer, 10 parts of carbon black, 0.1 parts of paraffin, 2 parts of stearic acid, 1 part of phosphate flame retardant, 0.5 parts of antioxidant, and 20 parts of plasticizer.
[0031] According to B.4.1 room temperature torsion test and B.4.2-25℃ low temperature torsion test in GB / T 33606-2017, the cable appearance was intact after 10,000 times of 1080° torsion test at room temperature and 5,000 times of 1080° torsion test at low temperature. After torsion, the cable was subjected to AC 50HZ 73.5KV voltage for 60 minutes without breakdown.
[0032] Comparative Example 1: The method is substantially the same as Example 1, except that no liquid amino-terminated nitrile rubber is added.
[0033] According to B.4.1 room temperature torsion test and B.4.2-25℃ low temperature torsion test in GB / T 33606-2017, the outer sheath of the cable cracked after 10,000 times of 1080° torsion test at room temperature and 5,000 times of 1080° torsion test at low temperature. After torsion, AC 50HZ 73.5KV voltage was applied for 60 minutes, and breakdown occurred.
[0034] Comparative Example 2: The method is substantially the same as Example 1, except that ordinary nitrile rubber is used instead of the liquid amino-terminated nitrile rubber.
[0035] According to B.4.1 room temperature torsion test and B.4.2-25℃ low temperature torsion test in GB / T 33606-2017, the cable appearance was intact after 10,000 times of 1080° forward and reverse torsion test at room temperature and 5,000 times of 1080° forward and reverse torsion test at low temperature. After torsion, AC 50HZ 73.5KV voltage was applied for 60 minutes, and breakdown occurred in both cases.
[0036] Comparative Example 3: The method is substantially the same as Example 1, except that the star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer is not added.
[0037] According to B.4.1 room temperature torsion test and B.4.2-25℃ low temperature torsion test in GB / T 33606-2017, the outer sheath of the cable cracked after 10,000 times of 1080° torsion test at room temperature and 5,000 times of 1080° torsion test at low temperature. After torsion, AC 50HZ 73.5KV voltage was applied for 60 minutes, and breakdown occurred.
[0038] Comparative Example 4: The method is basically the same as Example 1, except that no silicon dioxide nanotubes are added.
[0039] According to B.4.1 room temperature torsion test and B.4.2-25℃ low temperature torsion test in GB / T 33606-2017, the cable appearance was intact after 10,000 times of 1080° forward and reverse torsion test at room temperature and 5,000 times of 1080° forward and reverse torsion test at low temperature. After torsion, AC 50HZ 73.5KV voltage was applied for 60 minutes, and breakdown occurred in both cases.
[0040] Performance testing: The outer sheath layers prepared in Examples 1-5 and Comparative Examples 1-4 were made into test pieces; The tensile strength and elongation at break were tested according to GB / T1040.3-2006. The test piece was a 50 mm × 4 mm dumbbell specimen and the tensile speed was 250 mm / min.
[0041] The test results are shown in Table 1 below:
[0042] It can be seen from Table 1 above that the outer sheath layer prepared by the present invention has excellent tensile properties and can significantly improve the torsion resistance of the cable; From the comparison between Example 1 and Comparative Example 1, it can be seen that the addition of liquid end amino nitrile rubber plays a positive role in improving the tensile properties of the outer sheath layer; From the comparison between Example 1 and Comparative Example 2, it can be seen that the liquid end amino nitrile rubber has a better effect on improving the tensile properties of the outer sheath layer than ordinary nitrile rubber; From the comparison between Example 1 and Comparative Examples 3 and 4, it can be seen that the addition of star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer and silica nanotubes has played a positive role in improving the tensile properties of the outer sheath layer.
[0043] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A 35kV torsion-resistant cable for a wind turbine, characterized in that: It consists of a cable core and a ground wire, wherein the cable core and the ground wire are fixed by being covered by a torsion-resistant reinforcement layer and an outer sheath layer; The outer sheath layer is prepared from the following raw materials in parts by weight: 90-100 parts of polyvinyl chloride, 5-10 parts of liquid amino-terminated nitrile rubber, 5-10 parts of star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer, 10-20 parts of silica nanotubes, 3-5 parts of composite lead stabilizer, 5-10 parts of carbon black, 0.1-1 parts of paraffin, 1-2 parts of stearic acid, 1-3 parts of phosphate flame retardant, 0.1-0.5 parts of antioxidant and 20-40 parts of plasticizer.
2. The 35kV torsion-resistant cable for wind turbine generator according to claim 1, characterized in that: The cable core comprises a conductor, a conductor shielding layer, an EPR insulating layer and an insulating shielding layer from inside to outside.
3. The 35kV torsion-resistant cable for wind turbine generator according to claim 1, characterized in that: The torsion-resistant reinforcement layer is woven from Kevlar fibers.
4. The 35kV torsion-resistant cable for wind turbine generator according to claim 1, characterized in that: The preparation method of the star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer is as follows: The star-shaped polybutadiene is synthesized by a formic acid-hydrogen peroxide in-situ method to obtain a star-shaped epoxidized polybutadiene, and the star-shaped epoxidized polybutadiene is subjected to an incomplete esterification reaction with 2-bromoisobutyryl bromide under the action of water to obtain a star-shaped brominated polybutadiene, and then the star-shaped brominated polybutadiene is used as an initiator, cuprous chloride and cupric chloride are used as a catalyst and a regulator respectively, and N,N,N',N",N"-pentamethyldiethylenetriamine is used as a ligand, and methyl methacrylate polymerization is initiated by an ATRP method to finally obtain the star-shaped comb-shaped polybutadiene-g-polymethyl methacrylate copolymer.
5. The 35kV torsion-resistant cable for wind turbine generator according to claim 4, characterized in that: The molar ratio of epoxy group to 2-bromoisobutyryl bromide in the star-shaped epoxidized polybutadiene is 1:0.1-0.
8.
6. The 35kV torsion-resistant cable for wind turbine generator according to claim 4, characterized in that: The molar ratio of bromine atoms in the star-shaped brominated polybutadiene to methyl methacrylate is 1:10-40.
7. The 35kV torsion-resistant cable for wind turbine generator according to claim 1, characterized in that: The preparation method of silica nanotubes is as follows: The sepiolite is crushed and washed with deionized water, first added to a hydrochloric acid solution to remove impurities, the reaction solution is filtered, the solid is collected and washed thoroughly with deionized water, then added to a polyvinyl pyrrolidone solution, ultrasonically treated, and then sodium borohydride is added. The reaction solution is reacted at 50-70°C for 1-5h, and finally the product is collected, washed thoroughly with deionized water, and then dried.
8. The 35kV torsion-resistant cable for wind turbine generator according to claim 1, characterized in that: The phosphate flame retardant is any one or more combinations of tris(isopropylphenyl) phosphate, tris(2-chloroethyl) phosphate, and tris(2-chloropropyl) phosphate.
9. The 35kV torsion-resistant cable for wind turbine generator according to claim 1, characterized in that: The antioxidant is any one or more combinations of antioxidant 1010, antioxidant 1076, antioxidant 245, and antioxidant 168.
10. The 35kV torsion-resistant cable for wind turbine generator according to claim 1, characterized in that: The plasticizer is any one or more combinations of dimethyl phthalate, diethyl phthalate, di-n-butyl phthalate, dioctyl phthalate, butyl benzyl phthalate, and diisononyl phthalate.
Citation Information
Patent Citations
Special material for polychloroethylene insulating electrical casing pipe
CN101177512A
Method for quickly preparing uniform SiO2 nanotubes from meerschaum
CN104556074A
Polyvinyl chloride cable material and preparation method thereof
CN104861397A
Photoelectrical composite torsion-resistant medium-voltage wind power cable and method for manufacturing the same
CN104916369A
A method for preparing CPVC toughened and modified by silicone-acrylate rubber and nanometer calcium carbonate synergistically
CN107200976A